2017
DOI: 10.3389/fneur.2017.00149
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Association between Language and Cognitive Tests in Poststroke Aphasia

Abstract: BackgroundIndividuals with aphasia are often excluded from studies exploring poststroke cognition because so many of the standard cognitive assessments rely on language ability. Our primary objective was to examine the association between performance on cognitive tests and performance on comprehension and naming tests in poststroke aphasia. Second, we aimed to determine the association between language performance and a real-life measure of cognition (Kettle Test). Third, we explored the feasibility of adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…11,12 The increased focus on discourse has also turned attention to the role of cognition where planning, organizing, and monitoring longer sequences of output has provided an opportunity to actively consider the interaction between language and cognition in understanding and managing aphasia. While cognition has been recognized as important in the overall presentation of aphasia for many years, 13 the recent redefining of aphasia in the context of neural multifunctionality, that is, the dynamic and reciprocal interaction between language and (nonlanguage) cognition, 14 has raised several important issues for aphasia treatment. These include, for example, whether, and which, impaired and residual cognitive processes both interact with and support aphasia recovery, and how we might begin to systematically integrate cognitive processes into interventions for people with aphasia.…”
Section: Abstract: Discourse Intervention Multilevel Intervention Cmentioning
confidence: 99%
“…11,12 The increased focus on discourse has also turned attention to the role of cognition where planning, organizing, and monitoring longer sequences of output has provided an opportunity to actively consider the interaction between language and cognition in understanding and managing aphasia. While cognition has been recognized as important in the overall presentation of aphasia for many years, 13 the recent redefining of aphasia in the context of neural multifunctionality, that is, the dynamic and reciprocal interaction between language and (nonlanguage) cognition, 14 has raised several important issues for aphasia treatment. These include, for example, whether, and which, impaired and residual cognitive processes both interact with and support aphasia recovery, and how we might begin to systematically integrate cognitive processes into interventions for people with aphasia.…”
Section: Abstract: Discourse Intervention Multilevel Intervention Cmentioning
confidence: 99%
“…There is evidence to suggest that cognitive control is involved in a person's ability monitor one's own behaviour and detect problems in message transmission, to evaluate alternative methods of communication and/or to switch to another modality (Purdy, 2002). A number of studies have found switching impairments in PWA (e.g., Frankel et al 2007;Chiou & Kennedy 2009;Hachioui et al 2014;Wall et al 2017 as well as generation and selection of appropriate strategies (Frankel et al, 2007), both skills that are highly relevant when trying to switch from one modality to the next. Executive functioning has been linked to successful use of augmentative and alternative communication (AAC) (Nicholas et al, 2005(Nicholas et al, , 2011, while impaired executive functioning has been related to lack of switching between modalities during communication, despite having learned to use different modalities separately (Purdy et al, 1994).…”
Section: Multimodal Communicationmentioning
confidence: 99%
“…The relationship between speech-language pathology and neuropsychology can be illustrated by giving some specific neurological conditions as examples. Aphasias, for instance, are language disorders caused, most often, by stroke (6,7) . The neuropsychology contribution to aphasias is the use of cognitive and language evaluation batteries to diagnose and plan speech therapy for these cases (6,8) .…”
Section: Introductionmentioning
confidence: 99%